Antiretroviral medication adherence for people with HIV/AIDS - Nani Supriyatni; Lutfi Agus Salim; Arief Hargono; Febriyanti Febriyanti (AOSIS, 2023)
Background. People with HIV/AIDS require treatment with tiretrovirals (ARV) to reduce the amount of HIV virus in the body so it does not enter the AIDS stage, while people with AIDS require ARV treatment to prevent opportunistic infections with various complications. Objective. This study aimed to determine the ARV medication adherence of people living with HIV/AIDS (PLWHA), get information on the facts that influence PLWHA's use of ARV, analyze factors that influence PLWHA's use of ARV, and get information about treatment management for PLWHA. Methods. This study is a systematic review. Research information was obtained using the Google Scholar facility and an index of journal publications. Results. Factors related to ARV adherence in PLWHA include family support, level of knowledge, peer group support, side effects of medicine, motivation, behavioral skills, psychology of PLWHA patients, boredom, stigma, health care facilities, therapy guidelines, characteristics of comorbidities, perception, gender, health insurance, self-efficacy, social isolation, age, education level, income, duration of ARV treatment, support from health workers, spiritual motivation, and use of health services for the last three years. Conclusion. Adherence and family support play important roles in healing PLWHA. PLWHA must adhere to treatment with antiretrovirals. Family support plays an important role in healing PLWHA. It is suggested to the families of PLWHA that they give motivation and comply with the advice of health workers.